The Influence of Self-Efficacy and Teacher Academic Support on Students’ Time Management in Extracurricular Activities at Islamic Boarding Schools - Ahmad Farhan Rif’an Najib; Hafilda Anisa (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to determine the effect of self-efficacy and teacher academic support on students’ time management skills in extracurricular activities. In the context of modern education, student involvement in non-academic activities demands balanced time management skills. This study used a quantitative approach with an ex post facto design. The research sample amounted to 60 extracurricular coach teachers and subject teachers selected through the total sampling technique. Data were collected using a Likert scale questionnaire on three main variables: self-efficacy, teacher academic support, and student time management. Validity was tested through item total correlation, and reliability was tested with Cronbach’s Alpha. Data analysis was conducted using SPSS version 26 through multiple linear regression tests. The results showed that teacher self-efficacy had a significant effect on students’ time management ability, while teacher academic support did not show a significant effect, partially. However, simultaneously, both variables contributed 47.6% to time management. This finding emphasizes the importance of the teacher’s role in guiding students to manage time in a balanced manner between academic and extracurricular activities. Hopefully, this study can serve as a foundation for developing more responsive teaching strategies and teacher guidance, enabling students to manage their time effectively and achieve a balanced performance between academic and extracurricular activities, while also providing recommendations for schools to enhance professional development programs for teachers with a focus on time management guidance strategies